Partisipasi Masyarakat Pada Pelaksanaan Pengelolaan Sampah Dalam Meningkatkan Kepedulian Lingkungan Di Kelurahan Kedung Baruk - Ridha Hastika; Hasan Ismail (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
With increasing product and consumption patterns, more and more garbage is being produced every day. Reducing the amount of waste at its source by empowering communities is one of the strategies for tackling increased waste production. One of the underlying elements of the law applicable to the management of garbage in RT.01 Kelurahan Kedung Baruk is the participation of the public in the waste management. Data collection techniques include interviews and observations using qualitative descriptive techniques. The objective of this research is to describe and implement forms of public participation in the management of garbage in Kelurahan Kedung Baruk, how to deal with the accumulation of waste as a form of caring for the environment as well as to provide socialization of the importance of keeping the environment and managing the trash well and correctly for common well-being.